Pengaruh Promosi dengan Media Sosial Terhadap Keputusan Pembelian Sepatu Olahraga Ortuseight Pada Masyarakat Tanjung Morawa - Wibi Anindra Lukito; Aswin Fahmi D (Forum Kerjasama Pendidikan Tinggi, 2020)
An The purpose of this study was to determine and analyze the effect of Promotion with Social Media on the Purchase Decision of Ortuseight Sports Shoes in the Tanjung Morawa Community. The population of this study were 170 people from Dusun II Desa Limau Manis aged 17-25 years, with the sample of 43 people from the people of Gang Purwo Dusun II Desa Limau Manis aged 17-25 years. The analysis method used is descriptive statistical analysis and simple linear regression analysis. This type of research is associative research, and the data used are primary data and secondary data obtained through documentary studies and a list of statements measured using a Likert scale. Data were processed statistically using SPSS version 22 for windows, namely the t test model and the coefficient of determination (R2). The results of this study indicate that promotion with social media has a positive and significant effect on the purchasing decision of Ortuseight sports shoes in the Tanjung Morawa community. The amount of the dtermination coefficient (R Square) is 0.691, this means that 69.1% of the variation in the Promotion with Social Media variable can be explained by the Ortuseight Sports Shoes Purchase Decision variable, while the remaining 30.9% is explained by other variables not proposed in this study